Les relations halieutiques internationales du Mexique - Le Bail, Joël (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1987)
With the extension of the Exclusive Economic Zone, Mexico has been endowed with a tremendous oceanic potential. Although without any maritime history, the country embarked on the development of its marine biological resources ; an ailing ' 'agricultural revolution" was replaced by the , "blue revolution". An ambitious national plan for the development of its fisheries was set up; its implementation would improve the food supply situation, create thousands of jobs, increase exportations and, by turning out foreign fleets from its territorial waters, would also flatter Mexican nationalism. However, only part of these ambitions came to be. Lack of maritime know-how and a weak internal market have prevented Mexico from becoming free from external constraints. Although it has become an important producing country, yet it still remains dependent on the international market.